Aquaporin‐5 in breast cancer. Issue 5 (28th February 2022) - Bystrup, Malte; Login, Frédéric H.; Edamana, Sarannya; Borgquist, Signe; Tramm, Trine; Kwon, Tae‐Hwan; Nejsum, Lene N.
Abstract : The water channel aquaporin‐5 (AQP5) is essential in transepithelial water transport in secretory glands. AQP5 is ectopically overexpressed in breast cancer, where expression is associated with lymph node metastasis and poor prognosis. Besides the role in water transport, AQP5 has been found to play a role in cancer metastasis, migration, and proliferation. AQP5 has also been shown to be involved in the dysregulation of epithelial cell–cell adhesion; frequently observed in cancers. Insight into the underlying molecular mechanisms of how AQP5 contributes to cancer development and progression is essential for potentially implementing AQP5 as a prognostic biomarker and to develop targeted intervention strategies for the treatment of breast cancer patients.